2018
DOI: 10.37477/bip.v10i2.58
|View full text |Cite
|
Sign up to set email alerts
|

Urgensi Penerapan Anggaran Responsif Gender Di Pemerintah Daerah

Abstract: This study aims to know why gender responsive budgeting is not responsed by local government. Since it was issued by president as we know as Presidential Instruction Number 9 of 2000, there was no any significance changin in gender equality. This research was developed by some previous researches in Indonesia that found many regulations have setted to promote gender equality, but there was no significant action that showed by local government to implement it. So, this study try to seek what the obstacle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In contrast to Gainau (2020), which shows that the Salatiga government is at the middle commitment level of the three commitment levels, namely low, medium, and high. This means that the Salatiga government is still in the development stage on the implementation of gender-responsive budgets.…”
Section: Implementation Of Gender-responsive Budget To Maximise Gende...mentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast to Gainau (2020), which shows that the Salatiga government is at the middle commitment level of the three commitment levels, namely low, medium, and high. This means that the Salatiga government is still in the development stage on the implementation of gender-responsive budgets.…”
Section: Implementation Of Gender-responsive Budget To Maximise Gende...mentioning
confidence: 78%
“…These institutions can be from academics or from practitioners. Supported by the results of previous research conducted by Gainau (2020), which showed that where there are constraints in the implementation of a genderresponsive budget, then there is a strategy to implement gender-responsive budget efforts to form anticipation in the Manado City Government. The strategy includes the importance of understanding the concept of gender between government officials, how political will, and issues related to rejection of change, affirmation of technical capacity, mandatory accounting, and the importance of community group contributions to provide advice and overview for the Manado City Government when starting the implementation of gender-responsive budgeting.…”
Section: Gender-responsive Budget Strategymentioning
confidence: 89%
See 1 more Smart Citation
“…Gender mainstreaming (PUG) as a strategy in the planning system to promote equality between women and men in development that is integrated into every program or policy (Gainau, 2018;Natalis, 2020). This integration must be supported by seven prerequisites for implementing Gender Mainstreaming as stated in circulars from four ministries, namely commitments, policies, institutions, resources, disaggregated data, analytical tools, and community networks/participation (Harya, 2018;Penyusun, 2012).…”
Section: Mainstreaming Perspectivesmentioning
confidence: 99%